Design of Radiation Shielding in X-Ray Rooms: A Study on Radiological Protection - Aditya Surya Hartanti; Chomsin Sulistya Widodo; Zaenal Arifin; Johan Andoyo Effendi Noor (Diponegoro University Semarang Indonesia, 2026)
Radiation exposure protection is a critical aspect in the use of X-ray technology in the medical field. An effective radiation shielding design in X-ray rooms is not only important to protect patients, but also to ensure the safety of medical personnel who are routinely exposed to radiation. Alongside advancements in medical imaging technology, the design of X-ray rooms and shielding systems continues to evolve to meet increasingly stringent safety standards. This article aims to review recent approaches in radiation shielding design for X-ray rooms, with a focus on improving radiological protection. The study covers various types of materials used for shielding, such as lead, concrete, and alternative environmentally friendly materials, as well as new technologies in radiation protection systems. Additionally, it highlights optimal X-ray room design techniques, such as the placement of X-ray equipment, distance management, and room configuration, to minimize radiation exposure to unintended areas. Challenges in implementing shielding designs, including cost, space limitations, and compliance with safety regulations, are also thoroughly discussed. Furthermore, this article identifies the need for further research in this field, particularly regarding the development of more efficient and affordable shielding materials, as well as more innovative design approaches. The findings of this study are expected to provide new insights and practical recommendations that can be used by medical professionals, medical facility designers, and policymakers to enhance radiation safety standards in healthcare facilities.